Analysis of Flood Vulnerability and Rainfall Changes in the Angke-Pesanggrahan Watershed using Spatial Mapping - Fitria, Ratu Kenanga; Ruhiat, Yayat; Oktarisa, Yuvita (JURNAL GEOCELEBES, 2026)
This study analyzes flood vulnerability in the Angke-Pesanggrahan Watershed, Jakarta, which faces increased risks due to land-use changes. The study aims to calculate the 50-year return period flood discharge, map flood-prone zones, and formulate mitigation recommendations using spatial mapping. A quantitative approach was employed, analyzing 15 years of rainfall data from five stations. Methodology included data consistency testing, Spearman’s correlation, stationarity, and outlier identification, followed by regional rainfall analysis using Thiessen Polygons. The Log Pearson Type III distribution was applied for frequency analysis, and the Nakayasu Synthetic Unit Hydrograph method estimated flood discharge. Flood-prone zones were mapped using scoring and overlay techniques in a Geographic Information System (GIS). Results show that the 50-year flood discharge reaches 1.128 m3/s, exceeding existing river capacity. Mapping simulations identified flood depths of 3–6 meters in downstream areas, with high-risk zones concentrated in Northern Kembangan, Kedaung Kali Angke, Kapuk Muara, Kamal Muara, Eastern Cengkareng, and Northern Kedoya, where surface runoff contributes up to 90%. Spatial analysis categorized 257.18 km2 as non-prone, 92.14 km2 as moderately prone, 75.75 km2 as prone, and 58.57 km2 as highly prone. This study concludes that the Angke-Pesanggrahan Watershed, particularly the Cengkareng Drain section, requires urgent technical intervention, including river normalization and catchment area optimization. These findings provide a crucial spatial database for sustainable flood mitigation and risk-based decision-making in urban planning.